Lime stabilization for marginal sub-grade as capping layer for road construction - Kassim, Khairul Anuar; Shamshuddin, Mustafa Kamal (Universiti Teknologi Malaysia, 1999)
Cohesive soils, which contain high percentage of moisture have low values of California Bearing Ratio (CBR) and shear strength. Standard Specification for Road Works published by the Malaysian Public Works Department (JKR) suggests that these weak soils should be replaced with a suitable capping layer. However, instead of replacing the weak soil layer, stabilization by lime can also be carried out on cohesive soils. In this research, lime stabilization method was applied at the minimum strength of the soil to form capping layer. Cohesive soils with Plasticity Index (PI) of more than 20% and Clay Fraction (CF) exceeding 30% were used. Hydrated lime in the percentage of 5% by mixture was used as the stabilizing agent. CBR test were conducted on the stabilized soil samples and the result show strength development of more than 100% after a curing period of 28 days. This strength development in lime-stabilized soil was also observed experimentally by load testing of a road structure model which consists of lime-stabilized layer as the capping layer over a weak, clay sub-grade. Initially, observations are made on the ability of the road structure to reduce settlement of the sub-grade when load is applied. Unstabilized soil experienced over100% settlement when the load increased from 0.5kN to 1.5kN. a reduction in settlement from 70% to 100% was achieved for stabilized layer immediately after mixing. After 28 days, the settlement is almost negligible. The soil bearing capacity of stiff layer overlaying soft layer was determined using the theory proposed by Braja (1999). The theory is confirmed by the bearing capacity model study based on stabilized layer overlay soft soil conducted using 32cm x 32cm model box with 52cm in height. A number of 26 samples were prepared with 3 different stabilized layers i.e., 40, 60 and 80mm thick. These samples were cured for a period of 0, 7, 14 and 28 days. The bearing capacity was determined according to the theoretical analysis and from model testing. The bearing capacity increases with curing period and thickness of the capping layer. For the purpose of weight limit design, curing period of 28 days is considered. Weight limit design with the incorporation of geotechnical aspect is used to determine the maximum allowable vehicular load. This maximum allowable load is taken at a point before the ultimate bearing capacity of the sub-grade is exceeded. This approach of design provide an additional precaution against accessive vehicular load so as not to overstress the sub-grade.